2011
DOI: 10.4049/jimmunol.1101776
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class I Family Proteins Retard Systemic Lupus Erythematosus Autoimmunity and B Cell Lymphomagenesis

Abstract: Dysregulation of the T cell-dependent Ab response can lead to numerous immunological disorders, ranging from systemic lupus erythematosus to B cell lymphomas. Cellular processes governed by MHC class II proteins play a major role in this response and its dysregulation. The extent to which processes controlled by the diverse family of MHC class I proteins impact such autoimmune and neoplastic disorders, however, is less clear. In this study, we genetically dissect the contributions of individual MHC class I fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…39 Moreover, MIPs are the targets of several immune processes, including autoimmunity, graft rejection, GVHD, and the GVL effect. 5,6,35 Estimates suggest that the immunopeptidome comprises approximately 0.1% of the nonapeptide sequences (the typical length of MIPs) found in the proteome. 5 Despite the important role of MIPs in health and disease, we know little about their biogenesis except for the fact that they derive from DRiPs, the physical nature of which remains ill-defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Moreover, MIPs are the targets of several immune processes, including autoimmunity, graft rejection, GVHD, and the GVL effect. 5,6,35 Estimates suggest that the immunopeptidome comprises approximately 0.1% of the nonapeptide sequences (the typical length of MIPs) found in the proteome. 5 Despite the important role of MIPs in health and disease, we know little about their biogenesis except for the fact that they derive from DRiPs, the physical nature of which remains ill-defined.…”
Section: Discussionmentioning
confidence: 99%
“…MHC I-associated peptides (MIPs) play crucial roles in many processes, including the development and homeostasis of CD8 T cells, self/nonself discrimination, tumor immunosurveillance, tissue rejection, GVHD, and odorant-based mate selection. [1][2][3][4][5][6] Classic MHC I molecules are encoded by 3 genes in humans, HLA-A, HLA-B, and HLA-C, which have an astounding allelic diversity. 7 Genetic polymorphisms that distinguish HLA allomorphs affect mainly their peptide-binding groove.…”
Section: Introductionmentioning
confidence: 99%
“…In general, CD8 T cells are critical in limiting tolerance breaks in normal mice and they fail in lupus prone mice (55). Defects in CD8 mediated lupus down regulation have been reported in NZB/W (5658), MRL/lpr (59, 60) and BxSB lupus mice (61, 62). Also, Qa-1 restricted CD8 T cells have been reported to down regulate Qa-1 expressing Tfh cells and prevent lupus (63).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Jiang et al have demonstrated that MHC class Ib molecules activate a key population of CD8 + T-regulatory cells (Jiang et al 1995; Jiang et al 2005). When lacking functional CD8 + T-regulatory cells, mice develop a systemic lupus erythematosus-like syndrome, suggesting a role for these class Ib molecules in the suppression of autoimmunity (Kim et al 2011; McPhee et al 2011). While our study does not offer mechanistic insights, the demonstrated association between DLA-79 and immune-mediated disease supports further investigations regarding the role of class Ib molecules in these conditions.…”
Section: Discussionmentioning
confidence: 99%